Reproductive outcomes following induced abortion: a national register-based cohort study in Scotland. Issue 4 (6th August 2012) - Bhattacharya, Siladitya; Lowit, Alison; Bhattacharya, Sohinee; Raja, Edwin Amalraj; Lee, Amanda Jane; Mahmood, Tahir; Templeton, Allan
Abstract : Objective: To investigate reproductive outcomes in women following induced abortion (IA). Design: Retrospective cohort study. Setting: Hospital admissions between 1981 and 2007 in Scotland. Participants: Data were extracted on all women who had an IA, a miscarriage or a live birth from the Scottish Morbidity Records. A total of 120 033, 457 477 and 47 355 women with a documented second pregnancy following an IA, live birth and miscarriage, respectively, were identified. Outcomes: Obstetric and perinatal outcomes, especially preterm delivery in a second ongoing pregnancy following an IA, were compared with those in primigravidae, as well as those who had a miscarriage or live birth in their first pregnancy. Outcomes after surgical and medical termination as well as after one or more consecutive IAs were compared. Results: IA in a first pregnancy increased the risk of spontaneous preterm birth compared with that in primigravidae (adjusted RR (adj. RR) 1.37, 95% CI 1.32 to 1.42) or women with an initial live birth (adj. RR 1.66, 95% CI 1.58 to 1.74) but not in comparison with women with a previous miscarriage (adj. RR 0.85, 95% CI 0.79 to 0.91). Surgical abortion increased the risk of spontaneous preterm birth compared with medical abortion (adj. RR 1.25, 95% CI 1.07 to 1.45). The adjusted RRs (95% CI) for spontaneous preterm delivery following two, three and four consecutive IAs were 0.94 (0.81 to 1.10), 1.06 (0.76 to 1.47) and 0.92 (0.53 to 1.61), respectively. Conclusions: The risk of preterm birth after IA is lower than that after miscarriage but higher than that in a first pregnancy or after a previous live birth. This risk is not increased further in women who undergo two or more consecutive IAs. Surgical abortion appears to be associated with an increased risk of spontaneous preterm birth in comparison with medical termination of pregnancy. Medical termination was not associated with an increased risk of preterm delivery compared to primigravidae.